Estimating carbon stocks and biomass accumulation in three different agroforestry patterns in the semi-arid region of Pakistan. Issue 6 (29th November 2021) - Yasin, Ghulam; Ur Rahman, Shafeeq; Farrakh Nawaz, Muhammad; Qadir, Ihsan; Zubair, Muhammad; Gul, Sadaf; Safdar Hussain, Muhammad; Zain, Muhammad; Athar Khaliq, Muhammad
Abstract: Due to higher atmospheric greenhouse gasses concentrations, global warming is undoubtedly the most critical environmental issue that needs an immediate solution. Agroforestry has attained worldwide recognition to cope with this global problem due to its greater potential to sequester atmospheric carbon dioxide along with other ecosystem services, including food security. However, quantitative information about the biomass and carbon sequestration in poplar-maize agroforestry systems is not available in semi-arid climatic zones in Pakistan. The current study was carried out to evaluate the vegetation biomass and carbon stocks under three poplar-maize agroforestry planting patterns under semi-arid climatic conditions in a subdivision Jaranwala, District Faisalabad, Pakistan. The data was collected in three agroforestry patterns like; A (192 trees ha −1 ), B (255 trees ha −1 ), and C (296 trees ha −1 ). Allometric equations were used to estimate the biomass and carbon stock in plant species. Results showed that the poplar tree carbon stock among three planting patterns was significantly different, with maximum carbon stock of 35.62 t ha −1 in pattern C, and it was 8% and 33.5% greater than the carbon stock of pattern B and pattern A, respectively. The maximum aboveground biomass assimilated by maize crop was (11.95 t ha −1 ) in pattern B, and it was 10.3% and 3.6% greater than pattern A and pattern C, respectively. The grain yield was highest in pattern A as compared to the other two patterns. Additionally, the maximum soil carbon stock in soil was estimated (22.72 t ha-1) in pattern C, at 0-15 cm depth, while it was 13.42% and 6.61% greater than pattern A and pattern B, respectively. In conclusion, the findings of this study suggested that pattern C with maximum biomass production and carbon stocks is the optimum poplar maize planting pattern in requisites of both financial and environmental benefits in the form of carbon sequestration.